Development of parameters for the production of biomass and biohydrogen from brewer’s grain - A. Toleugazykyzy; D. Tlevlessova; A. Samadun; R. Bekbayeva (Eurasian Journal of Physics and Functional Materials, 2021)
In this work, suitable pretreatment conditions have been studied to increase hydrogen production by dark fermentation of brewer’s grain (BG). All samples with different concentrations of raw materials were tested: treatment with sulfuric acid with a concentration of 1.5%, autoclaving at 121 ◦C, purification from impurities by filtration, centrifugation and calibration of the pH of the medium to 7.5 units. The choice of acid hydrolysis is due to the fact that this type of pretreatment is the most suitable for the further commercialization of this technology. Also, pretreatment performs the task of suppressing methanogens and creating conditions for the life of hydrogen-producing bacteria. Experiments were carried out under mesophilic conditions ( 37 ◦C) using wild-type and multiple mutant E. coli. The highest sugar yields were obtained at a 4% concentration of brewer’s grains and in the presence of a concentration of 1.5% sulfuric acid in the original substrate. The results of the experiments showed that brewer’s grains are a valuable product as a source of carbon and energy for microorganisms in the production of biohydrogen, as well as for the production of biomass for further production of value-added products.